2014
DOI: 10.3389/fgene.2014.00206
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary analysis of the cystatin family in three Schistosoma species

Abstract: The cystatin family comprises cysteine protease inhibitors distributed in 3 subfamilies (I25A–C). Family members lacking cystatin activity are currently unclassified. Little is known about the evolution of Schistosoma cystatins, their physiological roles, and expression patterns in the parasite life cycle. The present study aimed to identify cystatin homologs in the predicted proteome of three Schistosoma species and other Platyhelminthes. We analyzed the amino acid sequence diversity focused in the identifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 61 publications
(116 reference statements)
2
14
0
Order By: Relevance
“…nipponicum cysteine peptidase inhibitor (EnStef) displays the typical length of type I cystatins (98 amino acids) and shares most of its sequential and structural characteristics with other type I cystatins, which are also known under the name stefins (I25A subfamily) 6 . Similarly to other platyhelminth stefin orthologs identified by combined computational approach 35 , EnStef lacks a signal peptide and the PW motif, but include the QxVxG and LP domains.…”
Section: Discussionmentioning
confidence: 99%
“…nipponicum cysteine peptidase inhibitor (EnStef) displays the typical length of type I cystatins (98 amino acids) and shares most of its sequential and structural characteristics with other type I cystatins, which are also known under the name stefins (I25A subfamily) 6 . Similarly to other platyhelminth stefin orthologs identified by combined computational approach 35 , EnStef lacks a signal peptide and the PW motif, but include the QxVxG and LP domains.…”
Section: Discussionmentioning
confidence: 99%
“…microstoma and T . solium [ 19 ]. In addition, excepting cestode cystatins, all predicted models of platyhelminth stefins and cystatins exhibited the similar conserved α-helix and β-pleat and the functional hydrophobic edge features that find in the human stefin [ 33 , 51 ] and chicken cystatin models [ 32 ], respectively (not shown).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, some studies have shown that nematode cystatins modulate host immune responses [ 13 16 ]. However, little is known about the cestode cystatin superfamily and trematode cystatin superfamily [ 17 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…The hairpin loop 1 containing the conserved QVVAG motif was a classic conformation of Cystatins. In TK-cystatin, the hairpin loop 2, formed by amino acid residues between two C-terminal β-sheet included conservative hydrophobic LP residues that was absence or replaced by PW in other cystatins (Cuesta-Astroz et al 2014).…”
Section: D Structure Of Tk-cystatin and Molecular Dockingmentioning
confidence: 99%